Penerapan Budaya Kaizen pada Kinerja Karyawan Diindustri Perbankan: Literature Review - Ilham Pauzi; Ana Aulia Setyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The culture applied by an organization or company is an important concern for employees and companies to support productivity and sustainable innovation, one of which is the application of Kaizen culture. So that the purpose of this study is to provide insight related to the application of kaizen culture in the banking industry. Through literature studies, research is made based on previous studies. This research discusses how the application of kaizen culture in the banking industry is able to have an impact in improving the operational efficiency of an organization or company, such as the PDCA Cycle in the kaizen concept which emphasizes continuous improvement and empowerment of employees to participate in the improvement process, the concept of the 5S movement which serves as the basis for developing a mentality of continuous improvement and quality awareness among employees. The implementation of Kaizen culture has brought significant impact in improving employee engagement in the Indonesian banking sector. Through active participation in Kaizen initiatives, employees feel more engaged, motivated, and committed to their work, which in turn can bring benefits to both employees and the company as a whole.